(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This article examines the study of the genre of the historical novel and its evolution poses a number of problems for researchers: in particular, the question of defining the concept of "historical novel" has not been resolved at the present time. Despite the many points of view expressed, it was not possible to derive a single definition. Nevertheless, literary critics are gradually "expanding" the genre framework, in modern works the question of the "decline" of the genre is touched upon less and less, questions are increasingly raised about the reasons for the undying popularity of the genre in the book market, about the connection of the historical novel with other novel forms.